The Effect of Audiolyfee Stimulation on the Optimization of Children's Potential and Talent: A Case Study in Banda Aceh - Nur Khalimah Purbasari; Cut Elfira (Green Publisher Indonesia, 2025)
Audio-based technology, such as Audiolyfe, offers innovative solutions to overcome this challenge. This study aims to analyze the effect of Audiolyfe stimulation on the development of children's potential and talents in Banda Aceh. Using a quantitative method and a quasi-experimental approach, this study involved 25 children aged 0-12 years who were selected through a purposive sampling technique. Data were collected through observation and questionnaires, then analyzed using descriptive statistics. The results showed that Audiolyfe stimulation has a significant effect on the development of children's potential and talents. A clear difference can be seen in the pretest and posttest results, where children who receive regular stimulation show an increase in creativity, cognitive ability, and enthusiasm for learning. These findings indicate that Audiolyfe can be an effective tool to support the optimization of children's abilities from an early age. With a structured approach, this technology makes a real contribution to preparing the younger generation to be more confident and have honed skills to face the challenges of the future.